Anatomy of Muslimah Clothing in The Qur'an (Study of Maudhu'i Abdul Hayy Al-Farmawi Method) - Hasanah, Mamluatul; Romziana, Lutviyah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research discusses the anatomy of Muslim women's clothing in the Koran using the maudhu'i method developed by Abdul Hayy Al-Farmawi. Muslim women's clothing in the Koran not only functions as a body covering but also as a manifestation of spiritual values and religious identity. This study aims to understand the clothing guidelines in the Koran and their relevance in modern social and cultural contexts. This research examines the verses of the Qur'an relating to Muslim women's clothing, such as An-Nur verse 31, Al-Ahzab verse 59, and Al-A'raf verse 26. Data was collected through documentation, surveys, semi-structured interviews, and field observations in Probolinggo Regency. The research findings show that the principles of dress in the Qur'an have deep spiritual and moral dimensions and remain relevant in the modern context. This research provides guidance for Muslim women to balance compliance with Sharia and adaptation to contemporary fashion trends and offers a new perspective regarding applying clothing guidelines in everyday life.